Evaluation of a pilot police-led suicide early alert surveillance strategy in the UK. Issue 4 (19th July 2017) - McGeechan, Grant James; Richardson, Catherine; Weir, Kevin; Wilson, Lynn; O'Neill, Gillian; Newbury-Birch, Dorothy
Abstract : Introduction: Those bereaved by suicide are at increased risk of psychological harm, which can be reduced with the provision of timely support. This paper outlines an evaluation of a pilot police-led suicide strategy, in comparison to a coroner-led suicide strategy looking at the number, and length of time it takes for deaths to be recorded for each strategy. Additionally, the police-led strategy offers timely contact from support services for bereaved individuals. We examined what impact this offer of support had on the capacity of support services. Methods: A mixed methods evaluation compared how long it took for suspected suicides to be recorded using both strategies. The number of referrals received by support services during the pilot strategy were compared with those from previous years. A feedback focus group, and interviews, were held with key stakeholders. Results: The coroner strategy was more consistent at identifying suspected suicides; however, reports were filed quicker by the police. Bereaved individuals were willing to share contact details with police officers and consent for referral to support services which lead to increased referrals. The focus group and interviews revealed that the pilot police strategy needs better integration into routine police practice. Conclusions: This strategy has the potential to deliver a real benefit to those bereaved by suicide; however, there are still aspects which could be improved.